Breast cancer awareness among Afghan refugee women in Turkey. (July 2022) - Kizilkaya, Mehmet Celal; Kilic, Sarah Sabrine; Bozkurt, Mehmet Abdussamet; Sibic, Osman; Ohri, Nisha; Faggen, Meredith; Warren, Laura; Wong, Julia; Punglia, Rinaa; Bellon, Jennifer; Haffty, Bruce; Sayan, Mutlay
Summary: Background Refugees and asylum-seekers have lower levels of cancer awareness and this contributes to low rates of screening and more advanced cancers at diagnosis, compared to non-refugee populations, due largely to reduced access to medical information and care. The global Afghan refugee population is rapidly increasing with the ongoing Afghan political crisis. The present study investigates breast cancer (BC) awareness among Afghan refugee women. Methods: A cross-sectional survey of Afghan refugee women residing in Turkey was performed in September 2021. A validated BC patient awareness assessment, the Breast Cancer Awareness Measure (BCAM), was used to assess participants' knowledge of seven domains of BC: symptoms, self-examination, ability to notice breast changes, age-related risk of BC, urgency of addressing changes in the breast, BC risk factors, and BC screening. BCAM was translated into patients' native language and administered verbally by a physician with the assistance of an official interpreter. Routine statistical methods were employed for data analysis. Findings: A total of 430 patients were recruited to the study. The response rate was 97·7% (420 patients). The median participant age was 35 years (range: 18 to 68 years). The majority of participants (84%) had no formal education. Most participants (96%) were married, and most (95%) were not employed. Awareness of warning signs of BC was low: only seven to 18% of participants recognized 11 common warning signs of BC. Participant use of breast self-exam (BSE) was low, with 82% of participants stating they rarely or never complete BSE. Zero of 420 patients reported ever seeing a physician for a change in their breasts. Awareness of risk factors for BC was also low: only 15% of participants recognized increasing age as a risk factor for BC, and other risk factors were only recognized by four to 39% of participants. Interpretation: BC awareness among Afghan refugee women is critically low. There is an urgent need to target this population for practical interventions to increase BC awareness, in addition to screening and earlier diagnosis. Evidence-based interventions include educational sessions in patients' native language and use of BSE and clinical breast examination for screening. Funding: American Society for Radiation Oncology (ASTRO) – Association of Residents in Radiation Oncology (ARRO) Global Health Scholar Grant, Dana-Farber Cancer Institute Jay Harris Junior Faculty Research Grant.